Research and Identity: Role-efficacy, Benchmarking, and the Identity Construction Process. Issue 3 (4th May 2019) - Hinojosa, Ramon; Williams, Allison; Edkin, Sarah; Sellers, Kyle; Elassar, Heba; Nguyen, Jenny
Abstract: In the spring of 2016, university students with little to no research experience volunteered to assist with surveying for a larger project on college success. Volunteers discussed their field experiences through written statements and semistructured interviews. Eighty log sheets and 14 in-depth interviews serve as the qualitative data for this study. We followed Braun and Clarke's (2006) Thematic Analysis approach and reviewed the log sheets for key themes. Based on the initial analysis, semistructured standpoint interviews with student volunteers explored the development of a nascent research-based identity. Findings suggest that students' research-based identity construction was a process that moved from low role-efficacy to emerging role-efficacy through the use of benchmarking and justification strategies that helped overcome negative emotions surrounding an initial sense of low role-efficacy with survey research tasks. We discuss how identity construction unfolded over time and suggest implications for this research.